2011
DOI: 10.3758/s13414-011-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

Incremental grouping of image elements in vision

Abstract: One important task for the visual system is to group image elements that belong to an object and to segregate them from other objects and the background. We here present an incremental grouping theory (IGT) that addresses the role of object-based attention in perceptual grouping at a psychological level and, at the same time, outlines the mechanisms for grouping at the neurophysiological level. The IGT proposes that there are two processes for perceptual grouping. The first process is base grouping and relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
109
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 205 publications
(342 reference statements)
11
109
0
Order By: Relevance
“…Perhaps the role of space in object-based selection is best illustrated in a recent study by Hollingworth, Maxcey-Richard, and Vecera (2012), who found interaction between space-and object-based attention within the same experimental paradigm. Consistent with the notion that there are linkages between lowerlevel spatial representations and higher-level spatially invariant representations at multiple levels of selection (Di Lollo, Enns, & Rensink, 2000;Hochstein & Ahissar, 2002;Roelfsema & Houtkamp, 2011;van der Velde & de Kamps, 2001), Hollingworth et al showed that whereas spatial attention forms a gradient across an attended object, the spread of this gradient is constrained by the boundaries of the object.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 68%
See 2 more Smart Citations
“…Perhaps the role of space in object-based selection is best illustrated in a recent study by Hollingworth, Maxcey-Richard, and Vecera (2012), who found interaction between space-and object-based attention within the same experimental paradigm. Consistent with the notion that there are linkages between lowerlevel spatial representations and higher-level spatially invariant representations at multiple levels of selection (Di Lollo, Enns, & Rensink, 2000;Hochstein & Ahissar, 2002;Roelfsema & Houtkamp, 2011;van der Velde & de Kamps, 2001), Hollingworth et al showed that whereas spatial attention forms a gradient across an attended object, the spread of this gradient is constrained by the boundaries of the object.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 68%
“…To date, the strongest physiological evidence supporting the within-group spread of attention has come from several recent studies by Roelfsema and colleagues (e.g., Roelfsema & Houtkamp, 2011;Wannig, Stanisor, & Roelfsema, 2011). In one experiment by Wannig et al (2011), monkeys were shown displays that consisted of two target bars and two distractor bars.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distractors that can be grouped based on such low-level cues can be rejected at once rather than on an item-by-item basis, leading to enhanced target detection (16)(17)(18)(19)(20)(21)(22). For example, when distracters can be grouped by color, search performance depends on the number of distracter groups rather than on the number of individual distracters in each group (17).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of experience on grouping have been attributed to feedback from object representations that facilitate grouping at a low level of processing (Kimchi & Hadad, 2002). Proposed neural mechanisms of grouping emphasize integration across stimulus representations by means of modifying intrinsic and longrange connections (Kapadia, Ito, Gilbert, & Westheimer, 1995;Roelfsema & Houtkamp, 2011). Increased connection strength is a fundamental process underlying perceptual learning, suggesting that training on grouping tasks can enhance integration of stimulus components and thereby improve perceptual grouping.…”
mentioning
confidence: 99%